PARAMETRIC CLASSIFICATION OF THE CONSUMER PROPERTIES OF THE GOODS FOR THE APPLICATION OF SEARCH FILTERS IN THE INTERNET STORE - SHAMRIN, Ruslan; LYZHNYK, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The development of information technologies, among which the Internet took one of the key places, the emergence and rapid growth of electronic commerce became the basis for the emergence of a new direction in the modern concept of interaction marketing - Internet marketing. Consumer validity and feasibility of using search filters in the Internet store is an important prerequisite for the effectiveness of the Internet store. After all, depending on the marketing validity and accuracy of the ranking of the applied product filters, it primarily depends on whether the buyer will find the product he needs on the store’s website and whether the purchase itself will be completed. That is, the quality of the parametric classification of the product’s consumer properties carried out by marketers directly affects the number of sales, and therefore the effectiveness of marketing companies’ promotion of goods via the Internet. The growth of competition in the field of electronic business and trade on the Internet requires increasing attention at all stages of product promotion, including the appropriate search engine optimization of the Internet store site and the appropriate setting of product filters. The article examines the necessity and expediency of conducting a parametric classification of the consumer qualities of the product in the process of developing a sequence of product filters that will be displayed on the main page of the online store. In addition, the author’s scheme of the sequence of the formation of the influence of the parametric classification of the consumer qualities of the product on the effectiveness of the online store is proposed, with the determination of positive and negative consequences at each of its stages, practical examples of the development of the parametric classification of the product are given and its results are compared with the product filters of the operating online store according to the corresponding a group of goods.